Relation between serum magnesium and outcome in patients with Escherichia coli sepsis - Yan Cao; Bangqi Hu; Wei Zhou; Zhengyu Liu; Yanfang Pei; Jiang Yu; Conglong Hu; Xin Liu; Xiaotong Han; Xiquan Yan; Liudang He; Ning Ding (BMC Infectious Diseases)
Abstract Objective Escherichia coli (E.coli) is the leading pathogen for deaths associated with antimicrobial resistance, making it the most problematic bacteria for human infections. This study aimed to investigate the association between serum magnesium levels and clinical outcomes in patients with E.coli sepsis. Method Data of E.coli septic patients were collected from the MIMIC-IV database. Patients were divided into three groups based on tertiles of serum magnesium levels. Three models were utilized, including the raw model (unadjusted), Model I (adjusted for age and gender), and Model II (adjusted for all potential confounding factors). Linear model and two-segment nonlinear model were established to examine the relationship between serum magnesium and 30-day, 60-day, and 90-day mortality rates. Kaplan-Meier survival curve analysis was performed to assess cumulative hazard of mortalities at 30-day, 60-day, 90-day based on tertiles of serum magnesium levels. Results A total of 421 E.coli septic patients were included and classified into tertiles: Q1(< 1.6 mg/dL), Q2 (1.6-1.9 mg/dL), Q3(> 1.9 mg/dL). In the Model adjusting for all potential confounders, for every 1 mg/dL increase in serum magnesium, there was a significant increase in 30-day, 60-day, and 90-day mortality rates, with odds ratios of 4.01 (95% CI 1.22–13.19, P = 0.022), 4.81 (95% CI 1.59–14.53, P = 0.005), and 4.45 (95% CI 1.52–12.96, P = 0.006) respectively. And linear model is more suitable for describing the relationship between serum magnesium levels and clinical outcomes. Kaplan-Meier analysis revealed that the cumulative hazard of mortalities at 30-day, 60-day, 90-day increased with the prolongation of hospital stay, particularly in the group with the highest serum magnesium level. Conclusion Increased level of serum magnesium is significantly associated with increased risk of 30-day, 60-day and 90-day mortality in a population of septic patients with E.coli infection.